2014
DOI: 10.21632/irjbs.7.2.79-90
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Labor Flexibility on Firm Performance in Indonesian Telecommunication Industry

Abstract: The purpose of this study is to analyze the influence of the dynamic business environment, the type of the company's business strategy, external labor flexibility, and internal labor flexibility on the firm performance. The unit of analysis in this study is the company, i.e. the companies in the telecommunications sector in Indonesia. This study uses primary data, through the distribution of questionnaires. Statistical technique used is partial least squares structural equation method (PLS-SEM). The findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Also, the study does not consider any possible moderator variables in the relationships between HR flexibility-performance and ambidexterity-performance. In the first case, the bibliography on functional flexibility introduces the moderating effect of some variables such as: the dynamism of the environment (Tracey, 2012;Ketkar and Sett, 2010;Natasaputra and Kusumastuti, 2016) or inter-organizational cooperation (Vela-Jiménez et al, 2014). In the second case, apart from the dynamism of the environment ( Jansen et al, 2006) a moderating effect has also been found in the ambidexterity-performance relationship of variables such as competitive intensity (Schulze et al, 2008), structural differentiation ( Jansen et al, 2012), resource endowment (Venkatraman et al, 2007) or leadership type ( Jansen et al, 2008).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the study does not consider any possible moderator variables in the relationships between HR flexibility-performance and ambidexterity-performance. In the first case, the bibliography on functional flexibility introduces the moderating effect of some variables such as: the dynamism of the environment (Tracey, 2012;Ketkar and Sett, 2010;Natasaputra and Kusumastuti, 2016) or inter-organizational cooperation (Vela-Jiménez et al, 2014). In the second case, apart from the dynamism of the environment ( Jansen et al, 2006) a moderating effect has also been found in the ambidexterity-performance relationship of variables such as competitive intensity (Schulze et al, 2008), structural differentiation ( Jansen et al, 2012), resource endowment (Venkatraman et al, 2007) or leadership type ( Jansen et al, 2008).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Two topics have been at the foreground of human resource (HR) management studies in recent years. The first is the utilization of high commitment and/or high performance work systems (HPWS) (Arthur, 1994;Pfeffer, 1994;Sanders et al, 2014) by organizations, whereas the second focuses on the forms of organization that can provide firms with workforce flexibility (Kalleberg, 2001(Kalleberg, , 2003Vela-Jiménez et al, 2014;De Lastra et al, 2014;Natasaputra and Kusumastuti, 2016). Labour flexibility is a very important topic in every organization, but even more so within highly labour-intensive sectors strongly affected by seasonality, as is the case of the hotel industry (Knox and Walsh, 2005;Hoque, 2013;Duncan et al, 2013;Yaduma et al, 2015).…”
Section: Introductionmentioning
confidence: 99%